Essential Oil Derived From Eupatorium adenophorum Spreng. Mediates Anticancer Effect by Inhibiting STAT3 and AKT Activation to Induce Apoptosis in Hepatocellular Carcinoma - Chen, Hao; Zhou, Bei; Yang, Jie; Ma, Xinhua; Deng, Shihao; Huang, Yun; Wen, Yanzhang; Yuan, Jingquan; Yang, Xinzhou (Frontiers in Pharmacology, 2018)
Eupatorium adenophorum Spreng. (EA) is a well-known noxious invasive species. Gas chromatography-mass spectrometry (GC-MS) analysis revealed that the essential oil derived from EA (EAEO) is mainly composed of sesquiterpenes. However, the pharmacological value of EAEO in hepatocellular carcinoma (HCC) remains largely unexplored. Herein, we investigated the anti-HCC activities of EAEO, and explored the potential mechanisms of EAEO-induced apoptosis. An MTT assay showed that EAEO inhibited HCC cell proliferation with little toxicity on normal liver cells. Wound healing and FACS assays revealed that EAEO suppressed HCC cell migration and arrested cell cycle, respectively. Moreover, EAEO promoted in vitro HCC cell apoptosis, and EAEO treatment inhibited HepG2 xenografts growth and enhanced apoptotic nucleus of xenografts in HepG2-bearing nude mice. Mechanistically, EAEO significantly decreased the ratio of Bcl-2/Bax and resulted in the activation of caspase-9 and -3. EAEO also reduced the expression of Grp78, which in turn relieved the inhibition of caspase-12 and -7. Meanwhile, EAEO suppressed the phosphorylation of STAT3 and AKT, indicative of its anti-HCC potential. In summary, we determined that EAEO treatment promoted HCC apoptosis via activation of the apoptotic signaling pathway in mitochondria and endoplasmic reticulum, as well as repressed the activity of STAT3 and AKT in HCC cells.